Автоматичні регулятори в багатоагентних системах управління технологічними комплексами - Ладанюк, Анатолій Петрович; Бойко, Регіна Олегівна; Смітюх, Ярослав Володимирович (My University, 2015)
В статті розглядаються підходи за якими оцінюється можливість створення ефективних систем автоматичного регулювання на основі багатоагентного підходу з використанням різних типів автоматичних регуляторів. При цьому особливої уваги заслуговує розробка інтелектуальних регуляторів, що базуються принципах нечіткої логіки та теорії нечітких множин. The article discusses approaches for evaluating the ability to create effective systems of automatic control based on multi-agent approach, using different types of automatic controllers. In particular sufficient detail the analytical basis of their descriptions of the different types and features of the contained use, as shown in the sales structure. In this case, special attention should be the development of intelligent controllers based principles of fuzzy logic and fuzzy set theory. Illuminated urgent task today, namely the creation of structures of cognitive agents of technological systems. It is shown that for technological facilities that operate in an uncertain and changing load, can also be used tabular methods of PID adaptive properties.
Keywords: кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка; регулятор нечіткий; багатоагентна система; fuzzy control; multi-agent systems; controller